Iron absorption during pregnancy is underestimated when iron utilization by the placenta and fetus is ignored. Issue 3 (2nd July 2020) - Delaney, Katherine M; Guillet, Ronnie; Pressman, Eva K; Caulfield, Laura E; Zavaleta, Nelly; Abrams, Steven A; O'Brien, Kimberly O
ABSTRACT: Background: Maternal iron absorption during pregnancy can be evaluated using RBC incorporation of orally administered stable iron isotope. This approach underestimates true maternal absorption of iron as it does not account for absorbed iron that is transferred to the fetus or retained within the placenta. Objective: Our objective was to re-evaluate maternal iron absorption after factoring in these losses and identify factors associated with iron partitioning between the maternal, neonatal, and placental compartments. Methods: This study utilized data from stable iron isotope studies carried out in 68 women during the third trimester of pregnancy. Iron status indicators and stable iron isotopic enrichment were measured in maternal blood, umbilical cord blood, and placental tissue when available. Factors associated with iron isotope partitioning between the maternal, neonatal, and placental compartments were identified. Results: On average, true maternal absorption of iron increased by 10% (from 19% to 21%) after accounting for absorbed iron present in the newborn ( P  < 0.001), and further increased by 7%, (from 39% to 42%, P  < 0.001) after accounting for iron retained within the placenta. On average, 2% of recovered tracer was present in the placenta and 6% was found in the newborn. Net transfer of iron to the neonate was higher in women with lower total body iron (standardized β = −0.48, P  < 0.01) and lower maternal hepcidin (standardized β = −0.66, P  < 0.01). In women carrying multiple fetuses, neonatal hepcidin explained a significant amount of observed variance in net placental transfer of absorbed iron ( R  = 0.95, P  = 0.03). Conclusions: Maternal RBC iron incorporation of an orally ingested tracer underestimated true maternal iron absorption. The degree of underestimation was greatest in women with low body iron. Maternal hepcidin was inversely associated with maternal RBC iron utilization, whereas neonatal hepcidin explained variance in net transfer of iron to the neonatal compartment. These trials were registered at clinicaltrials.gov as NCT01019096 and NCT01582802.